2014
DOI: 10.3174/ajnr.a4129
|View full text |Cite
|
Sign up to set email alerts
|

Visual Outcomes with Flow-Diverter Stents Covering the Ophthalmic Artery for Treatment of Internal Carotid Artery Aneurysms

Abstract: BACKGROUND AND PURPOSE: Flow-diverting stents can be used to treat intracranial aneurysms that are not amenable to treatment with coils. We analyzed ophthalmic consequences due to coverage of the origin of the ophthalmic artery by flow-diverting stents for the treatment of internal carotid artery aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
77
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(81 citation statements)
references
References 29 publications
2
77
2
Order By: Relevance
“…The authors speculated that rich collateral flows from the ECA might reduce the pressure gradient ensuring flow through the vessel covered by the flow diverter, which might increase the tendency for occlusion of the OphA in contradistinction to other side branches with terminal flow. Another recently published study reported visual outcomes after flow diversion treatment for OphA aneurysms 21. According to the study, aneurysms in the OphA originating from the aneurysmal sac showed higher rates of symptomatic thromboembolic complications (60%) than those of aneurysms in the OphA originating from the aneurysmal neck (16.7%).…”
Section: Discussionmentioning
confidence: 93%
“…The authors speculated that rich collateral flows from the ECA might reduce the pressure gradient ensuring flow through the vessel covered by the flow diverter, which might increase the tendency for occlusion of the OphA in contradistinction to other side branches with terminal flow. Another recently published study reported visual outcomes after flow diversion treatment for OphA aneurysms 21. According to the study, aneurysms in the OphA originating from the aneurysmal sac showed higher rates of symptomatic thromboembolic complications (60%) than those of aneurysms in the OphA originating from the aneurysmal neck (16.7%).…”
Section: Discussionmentioning
confidence: 93%
“…3–9 Many studies have concluded that the side branch occlusion rate is low and the clinical complications are not significant. However, Rouchaud et al 9 reported that new complications occurred in up to 39.3% of cases based on extensive physical examinations. Brinjikji et al reported that approximately one half of arteries show occlusion or decreased flow at follow-up if the ostia are covered with an FDS 15.…”
Section: Discussionmentioning
confidence: 99%
“…During the period in which this work was published, it was common practice to deploy more than one device in a telescopic fashion and one may argue that this might have had some influence. In a recently published study including 28 cases of carotid siphon aneurysms treated with FDS across the OphA ostium, Rouchaud et al 13 showed that although 85.7% had a patent OphA after endovascular treatment, 39.3% of patients presented a new ophthalmic deficit in an extensive ophthalmic evaluation performed 1 week after treatment.…”
Section: Discussionmentioning
confidence: 99%